Edutainment-Based Thematic Learning Strategies and Methods in the Independent Curriculum as an Effort to Overcome Multidisciplinary Learning Challenges in the Era of Society 5.0 - Azhari, Amalia Fauziah; Khadijah, Fairuza; Ulya, Nurul; Kamal, Rahmat (Universitas Pendidikan Indonesia (UPI), 2024)
Education in the era of Society 5.0 requires an adaptive and high-quality learning approach to tackle multidisciplinary learning challenges. This research aims to analyze and evaluate the implementation of edutainment-based thematic learning strategies in the independent curriculum at MI Walisongo Pajomblangan as an effort to address multidisciplinary learning challenges in the Society 5.0 era. The research method used was field study with a descriptive qualitative approach. Data were collected through obsevation, interviews and documentation at MI Walisongo Pajomblangan 01. The results showed that edutainment-based thematic learning in the independent curriculum at MI Walisongo Pajomblangan 01 was an effective solution for overcoming multidisciplinary learning challenges, allowing for interactive approaches, curriculum adaptation, and the development of students' social skills. Teachers utilized various edutainment strategies such as TGT, talking stick, and snowball using interactive multimedia. Through these strategies, students were facilitated to discuss and collaborate in groups to solve problems and were evaluated formatively and authentically to enhance active participation and understanding. Proactive steps were also taken by leveraging technology, teacher skill development, collaboration, and involving parents and the local community. It is hoped that the effectiveness of multidisciplinary learning continues to improve to prepare students to face global challenges.